Event Sebagai Pendukung Komunikasi Pemasaran Perusahaan Allo Bank dalam Membangun Kesadaran Merek - Hardjono, Baby Setiawaty; Setyanto, Yugih (Prologia, 2024)
PT. Allo Bank Indonesia Tbk (Allo Bank) is one of the digital banks in Indonesia under the auspices of CT Corpora. The purpose of this study is to explain event activities as a support for marketing communications carried out by Allo Bank in building brand awareness through the Allo Bank Festival 2022 which presents K-Pop groups. This study uses several supporting concepts, namely Communication, Marketing Communication, and Brand Awareness. The author uses qualitative research methods. The subject of this research is an event organizer and currently works in Allo Bank's digital customer service department, K-Pop fans, and also Allo Bank users. While the object of this research is the Allo Bank Festival 2022 event, which is a marketing communication activity used by Allo Bank in building brand awareness. Data from research results were obtained through interviews, observation, documentation, and literature studies. The results of the research show that the Allo Bank Festival 2022 event which presents K-Pop groups has succeeded in attracting audiences in building brand awareness. Marketing communications used by Allo Bank are events and publications which are included in the marketing communications mix, namely public relations. PT. Allo Bank Indonesia Tbk (Allo Bank) adalah salah satu bank digital di Indonesia yang berada di bawah naungan CT Corpora. Penelitian ini menjelaskan kegiatan event sebagai pendukung komunikasi pemasaran yang dilakukan oleh Allo Bank dalam membangun kesadaran merek lewat Allo Bank Festival 2022 yang menghadirkan grup K-Pop. Penulis menggunakan metode penelitian kualitatif dengan teknik pengumpulan data berupa wawancara panitia, penggemar K-Pop, dan nasabah. Hasil penelitian menunjukkan kegiatan event Allo Bank Festival 2022 yang menghadirkan grup K-Pop berhasil memberi daya tarik pada khalayak dalam membangun kesadaran merek. Komunikasi pemasaran yang digunakan Allo Bank adalah dengan menyelenggarakan event dan publikasi, termasuk dalam bauran komunikasi pemasaran yaitu hubungan masyarakat.